Ways to learn english idioms through literary works (Journal of Educational Sciences, 2021)
The article discloses the method of teaching a foreign language - teaching ideomes in the analysis of literary works. Idioms perform a highly communicative task. They are used to exchange opinions, figuratively convey meaning in speech, present speech in an expressive form. The article shows that the historically established limitations in correlating the meanings of phrases retained their influence from time to time. Thanks to these aspects, the language has covered all periods of development and is considered as a product of different periods, but as a whole.Idioms are used in both everyday and business life, both in everyday life and in official style, as well as in scientific and other styles of interaction.To teach English idioms, first of all, when composing teaching materials, teachers must choose literary works themselves and idiomatic expressions in it, both individually and in combination, that are accessible to students. At each new lesson, it is recommended to repeat the previous phrases, and remember in what context they were used. Each lesson, the teacher can include the learned expressions in new messages of his speech, so that there is a constant repetition, phrases heard in the teacher's speech are subconsciously absorbed into the students' memory.Keywords: teaching English, idioms, speech, analysis of literary works, semantic units, artistic creativity